Predatory Pricing on TikTok Shop and the Sustainability of Local Businesses in Indonesia: An Islamic Economic Analysis - Fahrurrozi; Achmad Room Fitrianto; Iftekhar Ahmed Robin (International Journal of Islamic Business and Economics (IJIBEC), 2024)
This study examines the impact of predatory pricing on TikTok Shop and its consequences for the sustainability of local businesses in Indonesia from an Islamic economic perspective. As Indonesia’s digital economy rapidly expands, the integration of e-commerce within social media platforms, such as TikTok Shop, has transformed market dynamics. This research employs a qualitative approach, utilizing semi-structured interviews with local business owners and a comprehensive document review of scholarly articles and official reports. The study investigates how TikTok Shop’s aggressive price undercutting disrupts fair competition and threatens the viability of small businesses. Findings indicate that predatory pricing practices significantly disadvantage smaller enterprises, reducing competition and increasing the risk of business closures. Such practices contradict Islamic economic principles, which emphasize fairness, ethical conduct, and social justice in market transactions. The study underscores the critical role of government regulation in ensuring ethical market practices and enforcing fair competition laws. By highlighting the detrimental effects of predatory pricing in social media commerce, this research advocates for stricter regulatory frameworks, aligned with Islamic economic principles, to safeguard local businesses and promote a just and sustainable economic environment. The findings provide valuable insights for policymakers and industry stakeholders, contributing to the broader discourse on ethical business practices in the digital economy.